Hasil Tanaman Tomat (Lycopersicum esculentum Mill.) Pada Beberapa Dosis Kompos Alang-Alang - Liz Yanti Andriyani; Irianto; Eva Ernawati Manurung (Agrotek, 2012)
The objective of the experiment was to observe the effect of several dosages of coarse grass compost to the yield of tomato. The experiment was conducted from December 2007 to May 2008 at Jambi University experimental station, which located in an altitude of 35 m above the sea level. The experimental design was randomized complete block design with 4 replications and 6 treatment level of dosages of coarse grass compost, ie.: a0: 0 ton ha-1 (no compost), a1: 5 ton ha-1, a2: 10 ton ha-1, a3: 15 ton ha-1, a4: 20 ton ha-1 and a5: 25 ton ha-1. The results showed that dosages of coarse grass compost significantly affected fruit set per plant, number of fruit per plant, fruit weight per plant, but no significantly affected age of the first flower initiation and age of the first harvest. The dosages of coarse grass compost on 25 ton ha-1 gave higher fruit set per plant, number of fruit per plant, fruit weight per plant than other treatments.